Dissemination of Carbapenem-Resistant Bacteria During the COVID-19 Pandemic in A Tertiary Hospital in Northern India - Khalid, Atif; Siddiqui, Obaid Ahmad; Amir, Syed Hasan; Nasreen, Farah (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Carbapenemase-producing Enterobacteriaceae (CRE), carbapenem-resistant Pseudomonas aeruginosa (CRPA) and Acinetobacter baumannii (CRAB) have spread rapidly in the recent years. Objective: To look for the impact of COVID-19 pandemic on carbapenemresistance. Methods: This retrospective, cross-sectional study was done, from March 2018 to April 2022, on an adult population of ICU patients who were found resistant to carbapenem group drugs in tracheal culture. Results: During the COVID-19 pandemic CRE, CRPA and CRAB infections were found significantly increased. Conclusion: Our results suggested the need to focus on CRE, CRPA and CRAB infections post-COVID-19. We explore how COVID-19 pandemic affects healthcare systems by amplifying AMR. Further studies are needed to understand the epidemiology and molecular profile of CRE, CRPA and CRAB associated infections post COVID-19. Screening is necessary when a patient has been in a hospital where carbapenem-resistant microorganisms are common, and every institution should have a specific policy in place for the management of organisms that are resistant to carbapenem that is periodically reviewed. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 309-313